PERANAN BUMDES KARANG DAPO SEBAGAI PENGGERAK EKONOMI PEMERINTAHAN DESA KARANG DAPO KECAMATAN PENINJAUAN KABUPATEN OGAN KOMERING ULU - Rakhmat Saleh (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
BUMDes Karang Dapo belonging to Karang Dapo Village is a business entity engaged in one business unit, namely renting tents and chairs. This BUMDes was established in 2017, classified as a young BUMDes. This is the background of this research whether BUMDes Karang Dapo has a big role for the economy of Karang Dapo village which has just been established and only has one business unit. This research is descriptive in nature which aims to describe, summarize various conditions, situations or variables that arise in the community that is the object of the research. The data collection technique used in this study used primary data in the form of observations and data sources, as well as secondary data in the form of interviews and documentation observations. The results of the study show that the management of BUMDes Karang Dapo has also not run well and its management has not achieved the objectives of implementing BUMDes, only as a complement. The main inhibiting factors are the lack of community participation, the lack of support from the district government and the private sector, as well as the absence of cooperation with third parties so that BUMDes Karang Dapo does not yet have any role as an economic driver for Karang Dapo Village.